Regional specializations in the European space - Philippe Rollet (Employment and regional development policy: Market efficiency versus policy intervention, 2004)
This paper examines certain aspects both of the geographical and international economy when analysing the phenomena of national and regional specialisation. First of all the factors of specialisation are examined by directing our attention particularly to the conclusions which can be drawn from the development of quality intra-branch exchanges within the European Union. The fact that these specialisations, influencing the economic performances of the territories (regions and nations), are not neutral will be subsequently pointed out. The specialisation scheme favoured by the realisation of the economic and monetary union thus has an important impact on the convergence between European economic systems, both regional and national.
hdl:10419/62287; http://EconPapers.repec.org/RePEc:zbw:arlssd:5
Keywords: 330